All‐Atom Simulations and Free‐Energy Calculations of Antibodies Bound to the Spike Protein of SARS‐CoV‐2: The Binding Strength and Multivalent Hydrogen‐Bond Interactions. Issue 5 (26th March 2021) - Lee, Hwankyu
Abstract: All‐atom simulations of various antibodies bound to the receptor‐binding domain (RBD) of the spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) are performed. Binding free energies calculated from umbrella sampling simulations show the strong binding between SARS‐CoV‐2 RBDs and antibodies, in agreement with recent experiments. Binding strengths of antibodies slightly differ, as further confirmed by calculating solvent accessible surface areas. Polar uncharged residues of RBD more predominantly bind to antibodies than do charged or hydrophobic residues of RBD. In particular, the binding between RBD and antibody is more significantly stabilized by multivalent hydrogen bonds of RBD residues (≈406th–505th) than by locally formed hydrogen bonds of only a few RBD residues (≈417th–487th or ≈487th–505th). Hydrogen‐bond analyses reveal key residues of RBD for strong hydrogen‐bond interactions between RBDs and antibodies, which help in the rational design of vaccine and drug molecules targeting the S protein of SARS‐CoV‐2. Abstract : Molecular dynamics simulations and free energy calculations of various antibodies bound to the receptor‐binding domain (RBD) of the spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) indicate that the RBD‐antibody binding is stabilized by multivalent hydrogen bonds of polar uncharged RBD residues, suggesting the key amino acids of RBD controlling the hydrogen‐bond interactions.